1999
DOI: 10.1038/sj.bjc.6690437
|View full text |Cite
|
Sign up to set email alerts
|

Platelet number and interleukin-6 correlate with VEGF but not with bFGF serum levels of advanced cancer patients

Abstract: SummaryWe have compared the platelet number and the serum concentration of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and interleukin-6 (IL-6) in 80 blood samples of 50 patients with advanced cancer. We have also measured the mitogenic effect of patient sera on endothelial cells in vitro in order to estimate the biological activity of serum VEGF. Serum VEGF concentration correlated with platelet number (r = 0.61; P < 10 -4 ). Serum IL-6 levels correlated with platelet coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
110
1
6

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(126 citation statements)
references
References 39 publications
9
110
1
6
Order By: Relevance
“…Several groups have confirmed the role of platelets in the storage of circulating VEGF-A (Verheul et al, 1997;Banks et al, 1998;Salgado et al, 1999;Gunsilius et al, 2000;Salgado et al, 2001).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 92%
See 4 more Smart Citations
“…Several groups have confirmed the role of platelets in the storage of circulating VEGF-A (Verheul et al, 1997;Banks et al, 1998;Salgado et al, 1999;Gunsilius et al, 2000;Salgado et al, 2001).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 92%
“…In a previous study we have shown that serum IL-6 correlates not only with the platelet count (illustrating its thrombopoietic property), with serum VEGF-A (illustrating the importance of IL-6 in the regulation of VEGF-A), but also with the VEGF-A load in platelets (Salgado et al, 1999). Since thrombopoietic cytokines, such as thrombopoietin (TPO) and interleukin-3 (IL-3), enhance VEGF-A expression in megakaryocytes, and, as is the case for TPO, in parallel with megakaryocytic differentiation, we hypothesised that IL-6 derived from primary tumour cells as well as A role for IL-6 in haemostasis and angiogenesis in cancer R Salgado et al from disseminated tumour cells might enhance VEGF-A expression in platelet progenitors much in the same manner (Imai et al, 1991;Mohle et al, 1997;Bobik et al, 1998;Salgado et al, 1999).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 94%
See 3 more Smart Citations